Sustainability and good living (buen vivir) in the province of Santa Elena, Ecuador: Contributions to the definition of compatible indicators - Zulaica, Laura; Álvarez Litben, Silvia (Documents d’Anàlisi Geogràfica, 2017)
The search and selection of indicators of sustainability is fundamental for measuring the “buen vivir” or good life (GL) of communities. In a first approach, the study evaluates the sustainability of parishes in the province of Santa Elena, Ecuador, using some indicators of the Plan Nacional para el Buen Vivir (2013-2017) in order to analyze the reach and limitations of their operability when applied at parish scale. A sustainability index comprising 28 indicators was obtained. The most beneficial indexes were found in parishes with highly urbanized areas, whereas the most critical ones were essentially rural. Many of the indicators showed a very weak correlation with the actual reality, while some limitations were observed, such as in the case of the population’s ethnicity. These findings are expected to open new doors for the research and adjustment of indicators of sustainability and GL at the local scale.